Torticollis: Multidisciplinary Clinical Evaluation and Management in Physiotherapy, Radiology, and General Medicine - Aljameeli, Razan Falah Matar; Salem Ali Alolayan; Tahani Saad Alshahrani; Mohammed Mahmoud Mousa Alameer; Mohammad Ahmad Sharahily; Bayan Abdulaziz Mustafa; Abdulmajeed Hussain Hassan Zughaibi; Badriyah Jamal Mosa Alkibari; Abeer Yahya Oqiesh; Naif Abdulaziz Nawi Alonazi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Torticollis, also known as twisted neck, is a common clinical condition characterized by abnormal head and neck posture resulting from involuntary muscular contractions or structural abnormalities. It affects individuals across all age groups and may range from benign, selflimiting presentations to manifestations of serious neurological or systemic disease. Due to its heterogeneous etiology and variable clinical presentation, torticollis requires careful multidisciplinary evaluation. Aim: This article aims to provide a comprehensive overview of torticollis, emphasizing its etiology, clinical presentation, diagnostic evaluation, and management strategies from a multidisciplinary healthcare perspective. Methods: A narrative clinical review approach was employed, integrating current medical, physiotherapeutic, neurological, and radiological perspectives on torticollis. The review synthesizes anatomical, epidemiological, and clinical data to support evidencebased assessment and treatment. Results: Torticollis is broadly classified into congenital and acquired forms, with etiologies including musculoskeletal, dermatogenic, ocular, vestibular, rheumatological, and neurogenic causes. Cervical dystonia represents the most prevalent form of adults, often involving the sternocleidomastoid and surrounding cervical muscles. Clinical evaluation remains the cornerstone of diagnosis, supported by imaging and laboratory investigations in selected cases. Management is individualized and commonly involves conservative measures such as physiotherapy, pharmacologic therapy, botulinum toxin injections, and, in refractory or structural cases, surgical intervention. Conclusion: Early recognition and accurate etiological diagnosis of torticollis are essential to optimize outcomes, minimize complications, and improve quality of life. A coordinated interprofessional approach is critical for effective longterm management.